Copeptin analysis in endocrine disorders - Moodley, Nareshni (Frontiers in Endocrinology, 2023)
Copeptin is cleaved from the same precursor as arginine vasopressin and is released in equimolar amounts with arginine vasopressin from the posterior pituitary in response to the same stimuli. Its stability in blood, quick and simple analysis and ease of automation make it much easier to analyse than arginine vasopressin and hence making it a suitable alternative than measurement of arginine vasopressin in endocrine disorders. Research has demonstrated the suitability of copeptin in adults for the differentiation of Arginine Vasopressin resistance and Arginine Vasopressin deficiency from primary polydipsia as well as early identification of Arginine Vasopressin deficiency post pituitary surgery however further research is still required in Syndrome of Inappropriate Antidiuretic Hormone and the pediatric population.